TECHNOLOGY CAPABILITY AND INNOVATION IN DRIVING COMPETITIVE ADVANTAGE FOR INDEPENDENT MUSIC ENTREPRENEURS - Sanitnarathorn, Pannawit; Wittayapreechakul, Trairat (Veredas do Direito, 2026)
This study examines the roles of technology capability and new product development in shaping competitive advantage among independent music entrepreneurs in the digital music era. As digital technologies continue to transform the music industry, independent artists increasingly rely on technological tools and innovative practices to compete in a dynamic and highly saturated marketplace. A quantitative research design was employed using survey data collected from 270 individuals actively engaged in the digital music ecosystem. The proposed conceptual model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that technology capability has a significant positive effect on both competitive advantage and new product development. In addition, new product development significantly influences competitive advantage and partially mediates the relationship between technology capability and competitive advantage. These findings suggest that technological capability alone is insufficient to ensure competitive success unless it is effectively translated into innovation. The study contributes to the literature by extending firm-level constructs to individual music entrepreneurs and highlights the importance of integrating technology and innovation for sustained competitiveness in the digital music industry.